(untitled) (Vietnam Journal of Community Medicine, 2021)
A cross-sectional study was carried out in 2017, with the method of cluster sampling (PPS) to select 30 communes/wards in 8 districts/cities in Thai Binh province. A total of 1450 adults from 25 ago or more the results showed that: The prevalence rate of hypertension was 29.8%, of which men account for 36.5%, 22.0% higher than that of women (p<0.05), mainly high blood pressure level 1 (42.3%), level 2 (35.4%) and level 3 (22.3%). The rate of hypertension tends to increase gradually by age group, the group aged 70 and over accounts for the highest proportion (36.4%), the age group 60-69 was 34.8%, the age group 40-59 was 31.5% and the lowest of 25-39 age group (16.1%) (p<0.05).